Sternal osteomyelitis caused by Aspergillus fumigatus in a patient with previously treated Hodgkin's disease. Issue 8 (1st August 2002) - Allen, D; Ng, S; Beaton, K; Taussig, D
Abstract : This report details the case of a 67 year old woman with sternal osteomyelitis caused by Aspergillus fumigatus . She was diagnosed with Hodgkin's disease in 1975 and was successfully treated with chemotherapy. A lobectomy for recurrence localised to the left lung was complicated nine years later by severe bronchiectasis, for which she required a total left sided pneumonectomy. At surgery, a non-invasive aspergillus was found. She presented eight years later with symptoms that were initially attributed to recurrence of Hodgkins's disease, but on investigation were found to be caused by fungal sternal osteomyelitis. Treatment with itraconazole suspension at a dose of 400 mg daily was successful.